The Social Effect of “Being Imitated” in Children with Autism Spectrum Disorder - Contaldo, Annarita; Colombi, Costanza; Narzisi, Antonio; Muratori, Filippo (Frontiers in Psychology, 2016)
There is evidence that ‘being imitated’ has social effects, and that the imitation of the child’s actions may be used as a strategy to promote social engagement in children with autism spectrum disorder (ASD). The observation of someone that imitates us recruits, indeed, neural areas involved in social cognition. We reviewed studies exploring the behavioral consequences of ‘being imitated’ in children with ASD. We aimed at assessing what are the social skills targeted by this strategy, and the factors that may improve the response. The ‘being imitated’ strategy improves social gazes, proximal social behaviors and play skills, particularly in children with low developmental level, and also when the strategy is implemented by children’s mothers. The ‘being imitated’ may be used as a tool in early intervention to improve social skills, helping to assess the effects of intervention at both behavioral and neural level.